Impact of easing COVID-19 restrictions on antibiotic usage in Eastern China using wastewater-based epidemiology - Jinxin Zang; Lufang Jiang; Yingying Wang; Yue Chen; Chaowei Fu; Barbara Kasprzyk-Hordern; Na Wang; Qingwu Jiang; Helen Lambert (Nature Communications)
Abstract Coronavirus Disease 2019 (COVID-19) emerged in December 2019, prompting the implementation of a “zero-COVID” policy in Mainland China. The easing of this policy in December 2022 led to a surge in COVID cases, which was believed to significantly increase antibiotic usage, potentially due to antibiotic misuse or increased coinfections. Our study aimed to compare antibiotic consumption and patterns before and after this policy adjustment. We utilised wastewater-based epidemiology (WBE) to analyse antibiotic levels in samples collected from five wastewater treatment plants in Eastern China during January and February of 2021 and 2023. 27 antibiotics were quantified using ultra-high performance liquid chromatography coupled with triple quadrupole tandem mass spectrometry (UPLC-MS/MS) and analysed via WBE, with the resulting estimates compared with catchment-specific prescription data. 23 antibiotics were detected in wastewater samples, with a substantial increase in usage in 2023 (ranging from 531% to 3734%), consistent with prescription data. Here, we show a significant rise in antibiotic consumption during the COVID-19 surge and this underscores the need for further investigation into the impacts of inappropriate antibiotic use in China.